Smoking and risk for amyotrophic lateral sclerosis: analysis of the EPIC cohort. - Gallo, V; Bueno-De-Mesquita, H; Vermeulen, R; Andersen, P; Kyrozis, A; Linseisen, J; Kaaks, R; Allen, N; Roddam, A; Boshuizen, H; Peeters, P; Palli, D; et al. (2009)
OBJECTIVE: Cigarette smoking has been reported as "probable" risk factor for Amyotrophic Lateral Sclerosis (ALS), a poorly understood disease in terms of aetiology. The extensive longitudinal data of the European Prospective Investigation into Cancer and Nutrition (EPIC) were used to evaluate age-specific mortality rates from ALS and the role of cigarette smoking on the risk of dying from ALS. METHODS: A total of 517,890 healthy subjects were included, resulting in 4,591,325 person-years. ALS cases were ascertained through death certificates. Cox hazard models were built to investigate the role of smoking on the risk of ALS, using packs/years and smoking duration to study dose-response. RESULTS: A total of 118 subjects died from ALS, resulting in a crude mortality rate of 2.69 per 100,000/year. Current smokers at recruitment had an almost two-fold increased risk of dying from ALS compared to never smokers (HR = 1.89, 95% C.I. 1.14-3.14), while former smokers at the time of enrollment had a 50% increased risk (HR = 1.48, 95% C.I. 0.94-2.32). The number of years spent smoking increased the risk of ALS (p for trend = 0.002). Those who smoked more than 33 years had more than a two-fold increased risk of ALS compared with never smokers (HR = 2.16, 95% C.I. 1.33-3.53). Conversely, the number of years since quitting smoking was associated with a decreased risk of ALS compared with continuing smoking. INTERPRETATION: These results strongly support the hypothesis of a role of cigarette smoking in aetiology of ALS. We hypothesize that this could occur through lipid peroxidation via formaldehyde exposure.